2013
DOI: 10.1242/dev.085548
|View full text |Cite
|
Sign up to set email alerts
|

Matrix adhesion polarizes heart progenitor induction in the invertebrate chordate Ciona intestinalis

Abstract: SUMMARYCell-matrix adhesion strongly influences developmental signaling. Resulting impacts on cell migration and tissue morphogenesis are well characterized. However, the in vivo impact of adhesion on fate induction remains ambiguous. Here, we employ the invertebrate chordate Ciona intestinalis to delineate an essential in vivo role for matrix adhesion in heart progenitor induction. In Ciona precardiac founder cells, invasion of the underlying epidermis promotes localized induction of the heart progenitor line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(52 citation statements)
references
References 62 publications
7
45
0
Order By: Relevance
“…Studies indicated that the cardiopharyngeal founder cells are exposed to a uniform distribution of FGF ligands and that TVC induction occurs via asymmetrical integrin-mediated adhesion with the epidermis (Cooley et al, 2011;Norton et al, 2013). These studies indicated that both TVCs are induced by essentially the same mechanism.…”
Section: The Tvcs Are Intrinsically Motile and Competent For Directedmentioning
confidence: 92%
See 2 more Smart Citations
“…Studies indicated that the cardiopharyngeal founder cells are exposed to a uniform distribution of FGF ligands and that TVC induction occurs via asymmetrical integrin-mediated adhesion with the epidermis (Cooley et al, 2011;Norton et al, 2013). These studies indicated that both TVCs are induced by essentially the same mechanism.…”
Section: The Tvcs Are Intrinsically Motile and Competent For Directedmentioning
confidence: 92%
“…The TVCs are born contacting the ventral epidermis (Nishida, 1987;Nishida and Satoh, 1985) and establish integrin-mediated adhesion to the epidermal extracellular matrix, which is required for TVC specification by polarizing sustained MAPK activity (Cooley et al, 2011;Norton et al, 2013). During their migration, TVCs maintain contact with the posterior trunk epidermis (Nishida, 1987;Nishida and Satoh, 1985).…”
Section: Secretion From the Epidermis Is Required For Tvc-tvc Adhesiomentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies have also revealed that matrix adhesion can profoundly influence growth factor signaling thereby impacting stem cell fate specification (Dave et al, 2014;Engler et al, 2006;Reilly and Engler, 2010;Yim and Sheetz, 2012). In contrast, relatively few studies have focused on the role of matrix adhesion in embryonic cell specification (Miller and Davidson., 2013;Brunet et al, 2013;Farge, 2011;Fonar et al, 2011;Martin-Bermudo, 2000;Norton et al, 2013). Thus, the dynamic, in vivo impact of matrix adhesion on embryonic cell fate decisions remains poorly characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has revealed a key role for matrix adhesion in differential heart progenitor induction ( Figure 1A 0 ). Prior to division, founder cells exhibit a broad domain of matrix adhesion along the ventral, epidermal boundary (Norton et al, 2013). This adherent domain correlates with a broad region of FGF receptor activation.…”
Section: Introductionmentioning
confidence: 99%